A comparative study of removal of Cr(VI) by ion exchange resins bearing quaternary ammonium groups. Issue 6 (June 2014) - Kusku, Ozge; Rivas, Bernabé L.; Urbano, Bruno F.; Arda, Müşerref; Kabay, Nalan; Bryjak, Marek
Abstract BACKGROUND Ion exchange resins based on poly[(4‐vinylbenzyl) trimethylammonium chloride] P(ClVBTA) and poly[(3‐acrylamidopropyl) trimethyl ammonium chloride] P(ClAPTA) were synthesized by radical polymerization. Metal ion uptake experiments were run with these synthesized resins and compared with the commercially available anion exchange resin Amberlite IRA‐400. RESULTS Retention of Cr(VI) was found to be independent of pH and the co‐existence of Cl− and SO42− ions for two resins. The sorption data obtained were evaluated using well‐known kinetic and adsorption isotherm models. The kinetic data obtained for the two resins fitted well to the pseudo‐second‐order model and the Langmuir isotherm. Besides, it was observed that temperature influenced slightly the sorption properties of the ion exchange resins synthesized in this study and commercially available ion exchange resin Amberlite IRA‐400. CONCLUSIONS The synthetic resins showed a better sorption performance than a commercially available ion exchange resin. The P(ClVBTA) and P(ClAPTA) resins exhibited greater and faster sorption than Amberlite IRA‐400. Sorption capacities of these ion exchangers were found to be in the order P(ClAPTA) > P(ClVBTA) > Amberlite IRA‐400. © 2014 Society of Chemical Industry.